KEWENANGAN JAKSA PENGACARA NEGARA DALAM PEMBATALAN PERKAWINAN (Studi Kasus Penetapan Pengadilan Agama Wates No.335/Pdt.G/2020/PA.Wt) - Ari Febriati (2023)
Marriage is declared valid if it is in line with religious rules and has fulfilled the legal conditions of a marriage as stipulated in the Marriage Law. If there is a violation of marriage as regulated by the law, a marriage annulment can be carried out. Based on the Determination of the Wates Religious Court No.335/Pdt.G/2020/PA.Wt, there is a conflict between the role of the State Attorney (JPN) in submitting a marriage annulment application and the role of an advocate, and there is legal uncertainty regarding the JPN being able to cancel a marriage against a man who is already married. This study aims to examine how the authority of the JPN in the annulment of marriage against the falsification of the status of a man who is already married. The method in this research is normative juridical. The result of the research is that the annulment of marriage requested by JPN on the basis of falsifying the status of a man who is already married is legally valid and legally binding and applies from the time of the marriage, which means that the marriage is considered to have never existed / occurred. There is a need for legal reform in the Marriage Law so that JPN has a definite legal position in canceling marriages related to polygamy.